2003
DOI: 10.1034/j.1600-0684.2003.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereology of the myocardium inLeontopithecus(Lesson, 1840) callitrichidae – primates

Abstract: Rare morphological features of the Leontopithecus cardiovascular system have been reported in the literature. The samples analyzed in this study came from 33 specimens of Leontopithecus from the collection of the Center of Primatology of Rio de Janeiro-FEEMA (CPRJ-FEEMA). Morphometry and stereological data were obtained from all animals. Adult body weights of L. rosalia were the lowest, the greatest being those of L. chrysopygus caissara; body weights of L. chrysomelas and L. c. chrysopygus were similar and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For stereological analyses of the volume density of connective tissue and the nucleocytoplasmic ratio of muscle cells, measurements were performed using the M42 testing system described elsewhere (Weibel, 1979;Pissinatti et al, 2003;Burity et al, 2004;Drabekova et al, 2005). The M42 testing system consists of 21 line segments and 42 points in a testing area.…”
Section: Methodsmentioning
confidence: 99%
“…For stereological analyses of the volume density of connective tissue and the nucleocytoplasmic ratio of muscle cells, measurements were performed using the M42 testing system described elsewhere (Weibel, 1979;Pissinatti et al, 2003;Burity et al, 2004;Drabekova et al, 2005). The M42 testing system consists of 21 line segments and 42 points in a testing area.…”
Section: Methodsmentioning
confidence: 99%
“…Muscle cell diameter was measured as the average of the longest lines drawn across the length and width of their cross-sections. The M42 testing system, which consists of 21 line segments and 42 points in a testing area, was used to measure connective tissue volume density and the nucleocytoplasmic ratio of muscle cells, as described elsewhere (Weibel, 1979;Pissinatti et al, 2003;Uscebrka et al, 2010). Connective tissue volume density (%) of breast muscle was calculated using the following formula:…”
Section: Methodsmentioning
confidence: 99%
“…These values are similar to those obtained in the present study for Callithrix kuhlii within the same group, the "Jacchus" group. Pissinatti et al (2003) studied the myocardium of 4 taxa of Leontopithecus (L. rosalia, L. chrysomelas, L. c. chrysopygus, and L. c. caissara), and reported that V V myocyte varied from 79.6 to 88.4, while the V V connective tissue 10.2 to 17.4. These values are important for comparison with those of this study and are similar because the animals, although from different species, belong to the same family, Callitrichidae.…”
Section: Discus Discus Discus Discus Discussion Sion Sion Sion Sionmentioning
confidence: 99%